A comparative case study of the employment of managerial staff in locally-owned and foreign-owned manufacturing enterprises in The Klang Valley Region - Ooi, Chooi Chooi (Universiti Sains Malaysia, 1982)
The managerial staff of any manufacturing firm, regardless of ownership, is the most important level of employees since they are the one who formulate policies and manage the firm. Their ability to manage technology, discovery and changes will create profit and growth to that firm. It is this category of human talent that plays a vital role in the economic growth of the country as a whole. The Klang Valley Region, being the most industrialized and populated region in the country, is also the focus of manufacturing enterprises of varying sizes and kinds. As such, it attracts management personnels from every States and, in fact, is the congregation of the largest force of management cadres in the country.